Aktivasi Otak pada Pembelajaran Anak Usia Dini - Munawarah, Siti; Mayasita, Tias; Khusna, Nadia; Khusna, Sakinah (IAIN Datuk Laksemana Bengkalis, Indonesia, 2024)
Children's learning is an important topic in the world of education. One interesting aspect of children's learning is brain activation. Brain activation in children's learning is an important process that influences how children learn, process information, and develop cognitive skills. Studies on brain activation in children's learning have shown that an adequate learning environment and appropriate stimulation can help optimize brain activation in children. In addition, developments in neuroimaging technology have allowed researchers to see children's brain activity as they learn, providing valuable insight into how the brain reacts to learning stimuli. The author aims to analyze and write a journal with the title